A novel method to perform endoscopic myotomy for Zenker’s diverticulum using submucosal dissection techniques - Kedia, Prashant; Fukami, Norio; Kumta, Nikhil A.; Kahaleh, Michel; Sharaiha, Reem Z. (Endoscopy, 2014)
A Zenker’s diverticulum arises from the cervical esophagus and results in a mucosal outpouching through Killian’s triangle. Treatment for symptomatic Zenker’s diverticulum is a diverticulotomy. Traditional therapy has been surgical cricopharyngeal myotomy via an open or transoral rigid endoscopic approach. Flexible endoscopic diverticulotomy for Zenker’s diverticulum has similar efficacy and is associated with fewer complications. Various techniques and devices have been used for myotomy including needle-knife, hook-knife, monopolar forceps, argon plasma coagulation, and harmonic scalpel. The limitation of current techniques is the difficulty in gauging the extent to which the most inferior part of the septum should be cut in order to treat the disease adequately while minimizing the risk of perforation and subsequent mediastinitis. In the cases described here, diverticulotomy using an endoscopic submucosal dissection technique was employed for muscular fiber exposure and septal dissection (myotomy) using a multipurpose knife. The utilization of a multipurpose knife with injection capability may further improve the success and safety of this procedure. Larger, randomized, prospective trials are needed to confirm this notion, standardize the technique, and identify the appropriate patient population for different endoscopic options.